Halftime re-warm up influences second half soccer performance: a competitive match analysis - Williams, J. H.; Hofffman, S.; Tegarden, D. P.; Russell, M. (Sport Performance & Science Reports, 2018)
Activities performed during the halftime interval of a soccer match can positively influence performance in the early stages of the second half (1,4,6,7,8,16). Accordingly, Russell et al. (12) present a detailed strategy for optimizing halftime practices; including, a brief (3-4 min) period of re-warm up (RWU). However, Towlson et al. (13) found that there are limitations to the application of a RWU during competition. Aim. While excellent justi cation exists for a halftime re-warm up, previous studies demonstrate a compromised ecological validity relative to competitive match conditions. As the nature of a competitive match may influence the e ects of a RWU, this study examined the relationships between workload performed during soccer halftime and performance during the initial stages of the second half. Methods: Athletes. Players from an NCAA Division I collegiate soccer team (n=13, 167.9±1.1 cm, 63.6±1.2 kg, mean SEM), competing in eighteen regular season competitive matches were analyzed. .